Exploring the potentials of Hagenia abyssinica (Bruce) J.F. Gmel for soil nutrient cycling in Galessa and the surrounding areas, central Ethiopia - Mekonnen, Kindu; Glatzel, G.; Sieghardt, M.; Bekele, K.; Alebachew, M.; Tserte, D. (International Livestock Research Institute, 2011)
The poster elaborates methodologies for collecting socioeconomic and biophysical information from H. abyssinica. It also demonstrates research results and discussions of the foliage nutrient concentrations, and soil macro and micronutrients under the Hagenia trees.